Person-Centered Care for Older Adults at Residential Care Facilities in the Iberian Peninsula: A Systematic Review - Barbosa, Maria Miguel (2022)
The aging of a population leads to a higher need for gerontological care. Person-centered care for older adults (PCCOA) offers a higher standard of quality at residential care facilities (RCFs). This systematic review is aimed at synthesizing Portuguese and Spanish studies on PCCOA, describing the process of implementation of PCCOA; exploring the impact of interventions based on PCCOA and determining the measurement tools used to evaluate PCCOA. This review was conducted in accordance with the PRISMA guidelines. Thirty-one of the included studies were conducted in Spain, and six were conducted in Portugal. Studies involved the development of models/recommendations, the promotion of resident participation in care processes and education/training. Their results indicated that PCCOA has positive outcomes for staff members and residents.